The Usage of Programming Software “The Library of Electronic Visual Aids “Algebra 7-9” During Algebra Learning in 7-9 Forms - Kreknin, В.А.; Lvov, М.С. (Journal of Information Technologies in Education (ITE), 2007)
The Programming software “The Library of Electronic Visual Aids “Algebra 7-9” for secondary institutions was developed for the computer support of algebra classes in 7-9 forms of secondary school. The present article describes the data about its basic characteristics features and possibilities.